Handgrip strength as a potential indicator of aging: insights from its association with aging-related laboratory parameters - Kemala Sari, Nina; Stepvia, Stepvia; Ilyas, Muhana Fawwazy; Setiati, Siti; Harimurti, Kuntjoro; Fitriana, Ika (Frontiers in Medicine, 2025)
IntroductionThe aging process is frequently associated with a decline in functional capacity, endurance, muscle quality, and overall quality of life. Examining aging-related biomarkers often requires significant time and financial resources, underscoring the need for a straightforward and practical indicator. This study aims to investigate the association between handgrip strength and aging-related laboratory parameters in the elderly population of Indonesia.MethodsA cross-sectional study was conducted involving 109 participants aged 60–82 years. Handgrip strength was measured using a Jamar hydraulic hand dynamometer and Jamar PLUS+ digital dynamometer. Aging-related laboratory biomarkers were defined as those indicating physiological aging processes.ResultsThe study revealed a significant association between handgrip strength and several aging-related laboratory parameters, including leukocyte count, absolute neutrophil count, absolute lymphocyte count, neutrophil/lymphocyte ratio, and erythrocyte sedimentation rate.DiscussionThese findings suggest that handgrip strength could serve as a cost-effective, non-invasive predictor of aging-related health status in older adults. Its practical utility highlights its potential for guiding health interventions targeting the elderly population.